Creating Images With the Stroke of a Hand: Depiction of Size and Shape in Sign Language - Lu, Jenny C.; Goldin-Meadow, Susan (Frontiers in Psychology, 2018)
In everyday communication, speakers not only describe, but they also depict. When depicting, speakers can take on the role of other people and quote their speech or imitate their actions. In previous work, we developed a paradigm to elicit depictions in speakers. Here we apply this paradigm to signers to explore depiction in the manual modality, with a focus on depiction of the size and shape of objects. We asked signers to describe two objects that could easily be characterized using lexical signs (descriptive elicitation), and objects that were more difficult to distinguish using lexical signs, thus encouraging the signers to depict (depictive elicitation). We found that signers used two types of depicting constructions (DCs), conventional DCs and embellished DCs. Both conventional and embellished DCs make use of categorical handshapes to identify objects. But embellished DCs also capture imagistic aspects of the objects, either by adding a tracing movement to gradiently depict the contours of the object, or by adding a second handshape to depict the configuration of the object. Embellished DCs were more frequent in the depictive elicitation context than in the descriptive conventional context; lexical signs showed the reverse pattern; and conventional DCs were equally like in the two contexts. In addition, signers produced iconic mouth movements, which are temporally and semantically integrated with the signs they accompany and depict the size and shape of objects, more often with embellished DCs than with either lexical signs or conventional DCs. Embellished DCs share a number of properties with embedded depictions, constructed action, and constructed dialogue in signed and spoken languages. We discuss linguistic constraints on these gradient depictions, focusing on how handshape constrains the type of depictions that can be formed, and the function of depiction in everyday discourse.